2020
DOI: 10.30958/ajp.7-4-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Translation Competence and Higher-order Thinking Skills of Novice Translators

Abstract: Higher-order thinking, known as higher order thinking skills (HOTS), is a notion of education improvement based on Bloom's taxonomy. The belief is that some types of learning involve more cognitive processing than others, but also have more generalized profits. The present study aims at investigating the relationship between translation competence along with its components and higher-order thinking skills of novice translators. To this end, 37 students of translation studies studying at the 5 th semester were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The current research aligns with the results of several previous studies concerning the direct impact of critical thinking on the translation technology proficiency of college students (Azin & Tabrizi, 2016;Ghaemi & Sadoughvanini, 2020;Jahromi & Suzani, 2016;Liu, 2019;Parham & Fahim, 2013). These studies found a positive correlation between the critical thinking and translation performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current research aligns with the results of several previous studies concerning the direct impact of critical thinking on the translation technology proficiency of college students (Azin & Tabrizi, 2016;Ghaemi & Sadoughvanini, 2020;Jahromi & Suzani, 2016;Liu, 2019;Parham & Fahim, 2013). These studies found a positive correlation between the critical thinking and translation performance.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies, such as Jahromi and Suzani (2016) further supported this association, showing that critical thinking, particularly deductive and inductive reasoning, significantly predicts translation performance. Ghaemi and Sadoughvanini (2020) extended this understanding, correlating higherorder thinking skills, including analyzing and creating, with translation quality. They argued that these skills impact the number and nature of translation errors, with 'analysis' contributing to extra-linguistic knowledge and 'creating' connecting new evidence for innovative reasoning in translation.…”
Section: Critical Thinking and Translationmentioning
confidence: 93%
“…They asserted that translators with higher levels of emotional intelligence are widely responsive to linguistic and non-linguistic relations, and they can produce high-quality translations. Ghaemi and Bayati [ 51 ], using structural equitation modeling, investigated the association between 34 qualified translators’ emotional Intelligence, burnout, and translation skill. Their study revealed a significant correlation between emotional intelligence and translation skill.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier studies have shown a significant relationship between critical thinking and translation quality (e.g., Liu, 2019;Ghaemi and Sadoughvanini, 2020;Saud, 2020;Li, 2022). In other words, translators' critical thinking facilitates the analysis of the source text and expedites the efficient translation of the message (Azin and Heidari Tabrizi, 2016).…”
Section: The Role Of Critical Thinking In Translation Performancementioning
confidence: 99%
“…Moreover, translators are required to employ critical thinking skills to ponder and interpret different translations, and come to a rational conclusion through deductive reasoning. Ghaemi and Sadoughvanini (2020) indicated that translation trainees’ higher-order thinking skills are significantly correlated with their translation quality. They justified their results based on Bloom’s taxonomy.…”
Section: Review Of Literaturementioning
confidence: 99%